Tourism development and human development: the case of the Santa Cruz city, Guanacaste - Morales Zúñiga, Luis Carlos (Población y Salud en Mesoamérica, 2011)
This paper analyzes the relationship between economic growth generated by tourism activities, and human development in the city of Santa Cruz, Guanacaste. It makes a special emphasis on the process of transforming the economic structure of the city of Santa Cruz, from a traditional economy to a service economy and its impact on human development in this place.